Guiding Light: Selections from the Holy Qur’an (American Journal of Islam and Society, 1987)
TranslationIn the name of Allah, the most benevolent, ever merciful.God commands justice, the doingOf good, and liberality to kithAnd kin, and He forbidsAll shameful deeds, and injusticeAnd rebellion: He instructs you,That ye may receive admonition.Surah 16:90If we look at the above verses we can see that the goal and essence of man’slife on earth is to live and follow the right course of life. The essence of thislife, on the positive side, is summarized in the first part of Surah 16:90 of theQur’an. The ultimate is for man to attain a life of justice ('adl), sincerity, concern,compassion, responsibility, and perfection (Ihsan) . In addition, oneshould exhibit the attributes of generosity and self-sacrifice in rendering helpto individuals and groups n every way and with regard to priorities (‘ita thawial qurba). On the negative and protective side, man should condemn andrefrain from committing or indulging in sinful, flagrant, tasteless, harmfuldeeds and actions (al Fahsha’ wa al-Munkar). Likewise he should avoid actsof injustice, usurpation, suppression or oppression against any person orrights of any human being (baghy).Recite what is sentOf the Book by inspirationTo thee, and establishRegular Prayer: for PrayerRestrains from shamefulAnd unjust deeds;And remembrance of GodIs the greatest (thing in life)Without doubt. And God knowsThe (deeds) that ye do.Surah 29:45 ...